Prevalence of Nitroimidazole-Refractory Giardiasis Acquired in Different World Regions, Sweden, 2008–2020 - Karin A. Ydsten; Joanna Nederby Öhd; Urban Hellgren; Hilmir Asgeirsson (Emerging Infectious Diseases)
Treatment-refractory giardiasis is an emerging clinical problem. Of 4,285 giardiasis cases identified during 2008–2020 in Stockholm, Sweden, 102 (2.4%) were nitroimidazole refractory. Among cases acquired in India, the percentage was high (64/545 [12%]) and increased over time. The region of acquisition needs to be taken into consideration when managing patients.